2014
DOI: 10.1002/ijc.28751
|View full text |Cite
|
Sign up to set email alerts
|

Cancer prevention by adult‐onset calorie restriction after infant exposure to ionizing radiation in B6C3F1 male mice

Abstract: Children are especially sensitive to ionizing radiation and chemical carcinogens, and limiting their cancer risk is of great public concern. Calorie restriction (CR) is a potent intervention for suppressing cancer. However, CR is generally not appropriate for children. This study, therefore, examined to see if adult-onset CR influences the lifetime cancer risk in mice after early-life exposure to ionizing radiation. Infant male mice (1-week-old) were exposed to 3.8 Gy X-rays, fed a control 95 kcal/week or CR 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 46 publications
2
43
0
Order By: Relevance
“…CR could decelerate the rate of aging and inhibit tumor formation in mammals [72][73][74]. It could also decrease the tumors that were induced by chemicals and IR in rodents and nonhuman primates [70,[75][76][77][78][79][80][81][82][83]. Even after exposure to IR, CR could still be effective for reducing cancer incidence in mice [82,83].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CR could decelerate the rate of aging and inhibit tumor formation in mammals [72][73][74]. It could also decrease the tumors that were induced by chemicals and IR in rodents and nonhuman primates [70,[75][76][77][78][79][80][81][82][83]. Even after exposure to IR, CR could still be effective for reducing cancer incidence in mice [82,83].…”
Section: Discussionmentioning
confidence: 99%
“…It could also decrease the tumors that were induced by chemicals and IR in rodents and nonhuman primates [70,[75][76][77][78][79][80][81][82][83]. Even after exposure to IR, CR could still be effective for reducing cancer incidence in mice [82,83]. These studies showed that dietary intervention could alter the phenotype and epigenotype in animal models [84], and demonstrated the feasibility of an active means to prevent or reverse the adverse effects from unbalanced diet or malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation is also a significant health risk factor, and is associated with both acute and chronic effects depending on the quality and dose of radiation. The effects of radiation on human health may be mediated, at least in part, by lifestyle-related factors, such as diet [ 8 10 ]. For example, the findings from epidemiological studies in nuclear plant workers suggest that lifestyle-related factors, including alcohol consumption, influence the adverse effects of radiation [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, Yoshida et al (7) observed a life-shortening of 59 days (7.1%) in calorie-restricted mice after 3 Gy acute irradiation, but of 113 days (14.4%) in non-restricted mice. Shang et al (9) found a reduced lifespan of 393 days (37.5%) in the calorierestricted group after 3.8 Gy acute irradiation and of 331 days (37.7%) in the non-restricted group. Thus, these studies showed that the life-shortening effect of acute radiation exposure is reduced or similar in calorie-restricted mice compared to that in non-calorie-restricted mice.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the lifespans of irradiated rats and mice were also shown to be improved by food or calorie restriction (7,8). More recently, Shang et al (9) demonstrated that calorie restriction in male B6C3F1 mice at an adult age (7 weeks old) was effective in reducing the neoplasm induction and life shortening induced by irradiation of 1-week-old infants, suggesting that the late effects of long-term radiation can be modified by calorie restriction.…”
Section: Introductionmentioning
confidence: 99%